Combined effects of self-myofascial release and dynamic stretching on range of motion, jump, sprint, and agility performance - Richman, E. D.; Tyo, BM.; Nicks, C. R. (The Journal of Strength and Conditioning Research, 2019)
Massage has been used as both a pre- and post-exercise modality with purported benefits to flexibility and athletic performance. This study was designed to determine the effect of a 6-minute protocol of self massage known as self-myofascial release (SMR) using a foam rolling device in conjunction with a general warm-up and sport-specific dynamic stretching (DS) session on flexibility and explosive athletic performance in a sample of 14 female collegiate athletes. After familiarization, participants completed 2 testing sessions that began with 5 minutes of jogging at a self-selected pace, followed by either a 6-minute foam rolling session (SMR) or 6 minutes of light walking (LW) and a subsequent 6-minute period of sport-specific DS. Sit-and-reach (SR) was measured after a general warm-up, the SMR, or LW session, and following DS, after which participants performed 3 trials each of squat jump (SJ), countermovement jump (CMJ), and drop jump (DJ). Two additional tests, the agility T-Test (TT) and a 10-yd short sprint (SP), were then performed. The change in SR after SMR was significantly greater than the change seen in SR after LW, although the total changes seen in each condition were not statistically different after the addition of DS. Squat jump and CMJ improved by 1.72 ± 2.47 cm and 2.63 ± 3.74 cm (p = 0.070, p = 0.070), with no significant change to DJ, SP, and TT. Self-myofascial release in the form of foam rolling after a general warm-up and preceding a DS session seems to improve SJ and CMJ with no detriment to flexibility, DJ, sprint, and agility performance in comparison with LW and DS.